Construct Validity of Porter Parental Acceptance Scale among Parents of Children With Autism Spectrum Disorder - Neneng Tati Sumiati; Nia Tresniasari; Syanindia Annisa Dewi (Journal of Research and Measurement in Psychology: JPPP, 2022)
Parental acceptance has an important role in determining successful parenting. Parents who can accept are positively sensitive to their children’s needs and children’s development. In this case, Porter Parental Acceptance Scale (PPAS) was used to measure the degree to which parents may be said to accept their children. This study aims to examine the construct validity of PPAS on 200 parents of autistic children in Indonesia. Data were collected using non-probability sampling techniques and administered through online questionnaires. Data were analyzed using confirmatory factor analysis (CFA). The result show that the model was classified as fit with Chi-Square = 611.33, df = 579, P-Value = 0.17045, RMSEA = 0.017. All items are valid, except item numbers 3, 5, 6, 8, 9, 34, 38. The implication is PPAS can be used to measures parental acceptance levels as indicated by the feelings and behaviors expressed toward their child.